Fifty moves a year: is there an association between joint physical custody and psychosomatic problems in children?. Issue 8 (28th April 2015) - Bergström, Malin; Fransson, Emma; Modin, Bitte; Berlin, Marie; Gustafsson, Per A; Hjern, Anders
Abstract : Background: In many Western countries, an increasing number of children with separated parents have joint physical custody, that is, live equally much in their parent's respective homes. In Sweden, joint physical custody is particularly common and concerns between 30% and 40% of the children with separated parents. It has been hypothesised that the frequent moves and lack of stability in parenting may be stressful for these children. Methods: We used data from a national classroom survey of all sixth and ninth grade students in Sweden (N=147839) to investigate the association between children's psychosomatic problems and living arrangements. Children in joint physical custody were compared with those living only or mostly with one parent and in nuclear families. We conducted sex-specific linear regression analyses for z-transformed sum scores of psychosomatic problems and adjusted for age, country of origin as well as children's satisfaction with material resources and relationships to parents. Clustering by school was accounted for by using a two-level random intercept model. Results: Children in joint physical custody suffered from less psychosomatic problems than those living mostly or only with one parent but reported more symptoms than those in nuclear families. Satisfaction with their material resources and parent–child relationships was associated with children's psychosomatic health but could not explain the differences between children in the different living arrangements. Conclusions: Children with non-cohabitant parents experience more psychosomatic problems than those in nuclear families. Those in joint physical custody do however report better psychosomatic health than children living mostly or only with one parent. Longitudinal studies with information on family factors before and after the separation are needed to inform policy of children's postseparation living arrangements.